2014
DOI: 10.1007/s12020-014-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mullerian hormone concentration during the third trimester of pregnancy and puerperium: a longitudinal case–control study in normal and diabetic pregnancy

Abstract: To assess if anti-mullerian hormone (AMH) concentrations decrease during the third trimester of pregnancy and puerperium and whether this is correlated to gestational diabetes mellitus (GDM). AMH serum concentrations were determined by ELISA, with lowest detection limit of 0.08 ng/ml, during the third trimester of pregnancy and puerperium in 34 patients with GDM and in 32 healthy control pregnant women. Three blood samples were collected at 28-32, 34-36 weeks' gestation and 40 days after delivery, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Prior studies of AMH in pregnancy have considered a mix of study samples and used different approaches . Using a cross‐sectional approach among 84 women, no significant differences were observed in AMH levels compared among those in the first trimester (n = 27), in second trimester (n = 21), in the third trimester (n = 13), and a nonpregnant (n = 15) group .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Prior studies of AMH in pregnancy have considered a mix of study samples and used different approaches . Using a cross‐sectional approach among 84 women, no significant differences were observed in AMH levels compared among those in the first trimester (n = 27), in second trimester (n = 21), in the third trimester (n = 13), and a nonpregnant (n = 15) group .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, cross‐sectional comparison of AMH levels among 554 women by trimester and postpartum suggested that levels decline over pregnancy and rapidly rise in the postpartum period . Decreasing AMH has been observed in the first few weeks of gestation among women seeking fertility care ( n = 85), and declines in AMH have been observed late in pregnancy in a prospective study of women with and without GDM during the third trimester, with significant decreases between 28 to 32 and 34 to 36 weeks of gestation …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two out of eight studies the association between AMH and gestational age was specifically evaluated (Köninger et al, 2013;La Marca et al, 2005). In the remaining six studies the association of AMH with fetal aneuploidy (n = 2) (Li et al, 2010;Plante et al, 2010), gestational diabetes mellitus (n = 1) (Gerli et al, 2015), fetal sex (n = 1) (Santillan et al, 2012), pre-term birth (n = 1) (Stegmann et al, 2015) and maternal adiposity (n = 1) (Nelson et al, 2010) was examined. Some of these studies reported AMH data separately for case and control groups and these data have also been extracted separately, where available.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…before term (n = 105) whilst the control group included women of white race who delivered at term (n = 95). In the study by Gerli et al (2015) the cases group included women with gestational diabetes (n = 34) and the control group was comprised of women with healthy, singleton pregnancies, without gestational diabetes mellitus (n = 32). In the study by Li et al (2010) the cases group included women with pregnancies affected by Down syndrome (n = 145) and the control group included women with pregnancies not affected by Down syndrome (n = 290).…”
Section: Selection Of Studiesmentioning
confidence: 99%